Halal food issues from Islamic and modern science perspectives - Ahmad Fadzillah, Nurrulhidayah; Che Man, Yaakob; Jamaludin, Mohammad Aizat; Rahman, Suhaimi Ab; Al-Kahtani, Hassan Abdullah M. (IACSIT Press, 2011)
Adulteration of food products has become a common issue in many countries. Adulteration is the act of intentionally take the form of substitution of one species for another whereby the food products from one species have been mixed intentionally with either similar substitute ingredient or cheaper species. For instance, food manufacturers often choose lard as a substitute ingredient for oil because it is relatively cheap and easily available. However, the usage of lard and pork is a serious matter in Islam. It is because any foods containing ingredients from pig sources are prohibited (haram) for Muslims to consume. Due to this restriction, it is crucial to develop scientific methods to detect the presence of lard and pork in halal food products. A reliable technique for detection of pork and lard adulteration in halal food products is necessary in order to protect Muslim consumers from intentional or non- intentional food fraud. This paper will highlight on the issues of adulteration of pork and lard in food products. It also attempts to scrutinize an Islamic perspective on lard which derives from pork sources.